Developing Historical Awareness in Elementary Teacher Education: A Narrative Literature Review from a Meaning-Making Perspective - Karina Wanda; Anik Ghufron; Ibnu Syamsi (Newinera Publisher, 2026)
This article examines the development of historical awareness in elementary teacher education through a meaning-making perspective. Responding to ongoing concerns about the limited relevance of history learning and the dominance of memorization-based approaches, this study employs a narrative and interpretive literature review to synthesize international research in history education. Historical awareness is conceptualized as a dynamic process involving sensitivity to the past, understanding the past, and self-representation in relation to history, each supported by specific meaning-making processes. The findings reveal three interconnected dimensions of historical meaning-making: experiencing historical temporality to cultivate sensitivity to the past, interpreting historical material through inquiry, narrative, and perspective-taking to develop understanding, and orienting toward practical life to construct historical presence and identity. The synthesis demonstrates that historical awareness emerges not as a linear set of competencies but as an integrative process shaped by cognitive, affective, cultural, and ethical engagement with the past. This study highlights the importance of pedagogical approaches that foreground reflection, personal connection, and ethical deliberation in history learning. The article concludes by emphasizing the relevance of meaning-making-oriented history education for preparing prospective elementary teachers to foster reflective and meaningful historical learning in schools.